2009
DOI: 10.1111/j.1349-7006.2009.01326.x
|View full text |Cite
|
Sign up to set email alerts
|

Antitumor effect of photodynamic therapy with chlorin‐based photosensitizer DH‐II‐24 in colorectal carcinoma

Abstract: While photodynamic therapy (PDT) has been recognized as a promising therapeutic modality for the treatment of various cancers and diseases, developments of effective photosensitizers are highly desired to improve the prospect for the use of PDT. In this study, we evaluated DH-II-24, a new photosensitizer, for antitumor PDT in vitro and in vivo. Loaded into human colorectal carcinoma cells (HCT116), DH-II-24 was primarily accumulated in mitochondria, lysosomes, and endoplasmic reticula. Administration of DH-II-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
17
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 32 publications
1
17
0
Order By: Relevance
“…Recently, we investigated the in vivo antitumor effects of PDT with DH-II-24, which exhibits several advantages such as strong absorption at relatively long wavelengths, minimal dark toxicity, and a shorter half-life in the body [Lim et al, 2009[Lim et al, , 2011]. Our results demonstrate that DH-II-24-mediated PDT could induce cell death through both apoptosis and necrosis in a PDT dose-dependent manner; intracellular ROS play a decisive role in the TG2-dependent apoptotic cell death induced by low-dose PDT (LDP), whereas high-dose PDT (HDP)-mediated necrotic cell death is controlled dominantly by intracellular Ca 2þ overload.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, we investigated the in vivo antitumor effects of PDT with DH-II-24, which exhibits several advantages such as strong absorption at relatively long wavelengths, minimal dark toxicity, and a shorter half-life in the body [Lim et al, 2009[Lim et al, , 2011]. Our results demonstrate that DH-II-24-mediated PDT could induce cell death through both apoptosis and necrosis in a PDT dose-dependent manner; intracellular ROS play a decisive role in the TG2-dependent apoptotic cell death induced by low-dose PDT (LDP), whereas high-dose PDT (HDP)-mediated necrotic cell death is controlled dominantly by intracellular Ca 2þ overload.…”
mentioning
confidence: 99%
“…KEY WORDS: PHOTODYNAMIC THERAPY; CELL DEATH, TISSUE TRANSGLUTAMINASE; REACTIVE OXYGEN SPECIES; INTRACELLULAR Ca 2þ P hotodynamic therapy (PDT) has been increasingly recognized as a selective treatment modality for various cancers and diseases [Triesscheijn et al, 2006;Lim et al, 2009;O'Connor et al, 2009;Robertson et al, 2009;Bredell et al, 2010]. Although an enormous number of studies have reported that PDT can induce many cellular and molecular signaling events that ultimately result in cell death, we remain far from a definitive understanding of the mechanisms of tumor cell killing because the efficiency and specific mechanism(s) of cell death are largely determined by a variety of parameters such as the concentration and intracellular localization of the photosensitizer, dose of light, cell genotype, and oxygen availability [Sharman et al, 1999;Nowis et al, 2005;Triesscheijn et al, 2006;Robertson et al, 2009].…”
mentioning
confidence: 99%
“…Recently, we reported a semi-in situ system through photodynamic therapy (PDT) to study the ultrastructure of microfilaments without additional treatment and under near-native conditions (Jung et al, 2009a). PDT is an anticancer modality that uses photosensitizers preferentially accumulated in cancer cells (Almeida et al, 2004;Ferreira et al, 2004;Tsai et al, 2005;Uzdensky et al, 2005;Lim et al, 2009). Subsequent activation of photosensitizer in target cells or tissues by light of an appropriate wavelength causes a cascade of biological events through various photophysical pathways, which induce production of reactive oxygen species, elevation of intracellular Ca 2+ , activation of caspases, and translocation of apoptosis-inducing factor, and ultimately result in cell death through apoptosis or necrosis (Almeida et al, 2004;Ferreira et al, 2004;Tsai et al, 2005;Yoo et al, 2009).…”
Section: Imaging In Semi-in Situ Environmentmentioning
confidence: 99%
“…Optical microscopy has contributed greatly to various studies of biological materials, including cells and tissues (Yi et al, 2004;Lim et al, 2009). However, the resolution of optical microscopy, due to the diffraction limit of the light source, is not sufficient to visualize subcellular structures.…”
Section: Introductionmentioning
confidence: 99%
“…25 Accordingly, developing photosensitizers with high specific accumulation properties is highly desired. 3 Carbohydrates are involved in various biological processes such as polyvalent interactions, 6 recognition, and some antibiotic agents. 7 Bound to a photosensitizer, they are able to improve solubility, decrease toxicity, and open the possibility of targeting saccharide-specific binding domains or metabolic pathways.…”
Section: Introductionmentioning
confidence: 99%